2015
DOI: 10.4018/978-1-4666-8348-8.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Obvious

Abstract: There is a general tendency, amongst policy and certain academic circles, to assume that universities are simple strategic actors capable and willing to respond to a well-articulated set of regional demands.In reality, however, universities are extremely complex organizations that operate in highly institutionalized environments and are susceptible to regulative shifts, resource dependencies and fluctuations in student numbers. Understanding universities' contributions -and capacities to contribute -to regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Similarly, in Sweden, which this paper emanates from, the role of academia has expanded from being an actor responsible for teaching and learning to being a knowledge producer in collaboration with society (Bjursell, Dobers and Ramsten 2016;Grafström, Jonsson and Klintman 2020). This change stems from an institutional shift in the higher education system that includes growing pressure from the political, public and private sectors on HEIs to engage in knowledge collaboration with other societal actors (Pinheiro, Geschwind and Aarrevaara 2014;Pinheiro, Benneworth and Jones 2015). This growing pressure has paved the way for numerous concepts, such as integrated science, social accountability, entrepreneurship, and overall economic relevance to society (Fumasoli 2019;Leydesdorff and Etzkowitz 1996;Yang 2018).…”
Section: Background: the Shifting Role Of Academia In The Knowledge S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in Sweden, which this paper emanates from, the role of academia has expanded from being an actor responsible for teaching and learning to being a knowledge producer in collaboration with society (Bjursell, Dobers and Ramsten 2016;Grafström, Jonsson and Klintman 2020). This change stems from an institutional shift in the higher education system that includes growing pressure from the political, public and private sectors on HEIs to engage in knowledge collaboration with other societal actors (Pinheiro, Geschwind and Aarrevaara 2014;Pinheiro, Benneworth and Jones 2015). This growing pressure has paved the way for numerous concepts, such as integrated science, social accountability, entrepreneurship, and overall economic relevance to society (Fumasoli 2019;Leydesdorff and Etzkowitz 1996;Yang 2018).…”
Section: Background: the Shifting Role Of Academia In The Knowledge S...mentioning
confidence: 99%
“…If the compatibility is weak, new initiatives or structures are typically rejected or decoupled from current practice (Maasen et al, 2017). Indeed, several studies have shown that societal collaboration tends to be decoupled from core internal HEI structures and that institutionalising such practices into the everyday HEI routines and norms is hard to reach (Pinheiro, Benneworth andJones 2015, Benner andSörlin, 2015). Our story brings fine-grained insights into the unfolding and consequences of this situation.…”
Section: (De)motivation To Engage In Collaborationmentioning
confidence: 99%
See 1 more Smart Citation